Reducing Mental Health Stigma Through Identification With Video Game Avatars With Mental Illness - Ferchaud, Arienne; Seibert, Jonmichael; Sellers, Nicholas; Escobar Salazar, Nivia (Frontiers in Psychology, 2020)
This study examines how playing a video game featuring a player-character with mental illness can positively impact mental illness stigma. We hypothesized that interactive gameplay would positively predict transportation into the story world. Then, transportation would predict identification with the main character. This identification should then reduce stigma in two ways: by lowering stereotyping and limiting participants’ desire for social distance. A two-factor, yoked experiment was designed utilizing Hellblade: Senua’s Sacrifice, a game praised for its accurate portrayal of psychosis. The main character, Senua, suffers from psychosis and must navigate her quest along with her own mental health. Players either played the first 45 minutes of the game or watched gameplay footage of other participants’ sessions. Transportation into the story world, identification with Senua, and the two aspects of stigma—stereotyping and social distance—were measured. Consistent with hypotheses, a structural equation model found an indirect path from gameplay to reduced social distance through first transportation and then identification. Players also reported higher levels of transportation than non-players, and that heightened transportation led to greater identification and then a lowered desire for social distance from the mentally ill. The indirect path to stereotyping was not significant. These results and implications are discussed in detail.